Association of Nighttime Systolic Blood Pressure With Left Atrial-Left Ventricular–Arterial Coupling in Hypertension - Sun, Qiaobing; Pan, Yu; Zhao, Yixiao; Liu, Yan; Jiang, Yinong (Frontiers in Cardiovascular Medicine, 2022)
Objective Hypertension (HT) induces left atrial (LA) and left ventricular (LV) dysfunction, and arterial stiffness increase. In this study, we investigated the association between LA-LV-arterial coupling and nighttime systolic blood pressure (BP) as well as BP circadian rhythm in essential hypertension. Methods We enrolled 290 HT patients. All subjects were evaluated by 2 dimensional speckle tracking echocardiography (2D-STE), ambulatory 24-hour BP monitoring (ABPM) and brachial–ankle pulse wave velocity (PWV). According to BP patterns, these patients were divided into two groups, which included dippers (n=111), patients with a >10% reduction in BP at nighttime; non-dippers (n=179), patients with a <10% reduction in BP at nighttime. 2D-STE based LA and LV strains were studied and the following parameters were measured, LV global longitudinal strain (GLS), LA reservoir strain (LAS-S), LA conduit strain (LAS-E), and LA booster pump strain (LAS-A). LA stiffness index (LASI) defined as the ratio of E/eʹ to LAS-S, and PWV-to-GLS ratio (PWV/GLS) were calculated to reflect LA-LV-arterial coupling. Furthermore, we also explored the correlation between LASI (or PWV/GLS) and ambulatory blood pressure indexes. Results LASI was significantly higher in non-dippers (0.29 (0.21, 0.41)) than dippers (0.26 (0.21, 0.33)) (p<0.05). PWV/GLS was significantly higher in non-dippers (-80.9 (-69.3, -101.5)) than dippers (-74.2 (-60.2, -90.6)) (p<0.05). LAS-S, LAS-E, LAS-A and LV GLS were significantly lower in non-dippers than dippers (p<0.05). Multivariate linear regression analysis revealed that nighttime systolic BP was independently correlated with LASI and PWV/GLS, even adjusted for multiple clinical risk factors, LVMI and LVEF. Conclusions The dipping pattern of BP was related to the abnormalities of myocardial mechanics and LA-LV-arterial coupling. However, absolute nocturnal systolic BP value maybe more important than BP circadian profile in the progression of abnormal LA-LV-arterial coupling.